2003
DOI: 10.1063/1.1558963
|View full text |Cite
|
Sign up to set email alerts
|

Crack formation in GaAs heteroepitaxial films on Si and SiGe virtual substrates

Abstract: We have determined the critical cracking thickness, or the thickness beyond which crack formation is favored, in GaAs films grown on Si and SiGe virtual substrates analytically and experimentally. The analytical model predicts a critical cracking thickness proportional to the biaxial modulus and the crack resistance of the GaAs film, and inversely proportional to the square of the thermal stress and a nondimensional crack resistance number Z. This Z number is determined by the mechanical properties of the GaAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 22 publications
2
89
0
Order By: Relevance
“…They demonstrated that the cracks, which have exhibited a dierent density along [110] and [110] depending on the residual strain, occurred after growth, and however, that the cracks did not have an important contribution to the strain relaxation inside the structures. Yang et al [17] observed an asymmetric crack array formation, caused by high thermal mismatches between in GaAs lms grown on Si and SiGe virtual substrates. Murray et al [18] reported a simple model describing the formation of cracks and their structural properties in tensile strained epilayers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that the cracks, which have exhibited a dierent density along [110] and [110] depending on the residual strain, occurred after growth, and however, that the cracks did not have an important contribution to the strain relaxation inside the structures. Yang et al [17] observed an asymmetric crack array formation, caused by high thermal mismatches between in GaAs lms grown on Si and SiGe virtual substrates. Murray et al [18] reported a simple model describing the formation of cracks and their structural properties in tensile strained epilayers.…”
Section: Methodsmentioning
confidence: 99%
“…Thermal strain depends on the thermal expansion coecients of the lm and substrate [21]. Especially, crack arrays in the thin lms are the result of high thermal mismatch [17]. Consequently, the strain energy in the structure can be relaxed via crack initiation [20].…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, the coefficient of thermal expansion (CTE) of GaAsP is lower than that of GaAs and closer to that of Si, reducing the likelihood of the III-V epi-layers cracking due to CTE mismatch between the films and the substrate. 8 In this work, we demonstrate GaAsP/InGaP transistors at a range of compositions from = 0.825 to = 1 (GaAs). These devices are grown on GaAs substrates rather than Si substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Additional problems arise for device applications in which the epitaxial structures have to be thick, such as in multi--junction solar cells, high brightness light-emitting diodes (LEDs) and power transistors. Here, dierent thermal expansion coecients of layers and substrates often cause wafer bowing [6] and layer cracking [7,8]. These may prohibit further wafer processing and/or cause device failure.…”
Section: Introductionmentioning
confidence: 99%